The correspondence of Ricardo Palma in the National Library of Peru - Pérez Garay, Carlos Alberto (2019)
This research paper describes and analyzes the vast correspondence that the Lima writer had with various characters from the political, economic, social and cultural spheres of Peru and the world, belonging to the Ricardo Palma Collection of the National Library of Peru.